Comparison of phenolic total ethanol extract of 70% and 96% carrot leaves and antibacterial activity test against Staphylococcus aureus - Lathifah, Jihan Najla; Wulandari, Wulandari (Journal of Health Management and Pharmacy Exploration, 2024)
Carrots (Daucus carota L.) are a plant that is widely used by the community, especially the tubers, while the leaves are not widely used and are only used as waste or animal feed. Carrot leaves contain secondary metabolites such as phenols, flavonoids, tannins, saponins, alkaloids, and steroids. Phenolic compounds are secondary metabolite compounds that are most abundant in nature. This compound can be used in the pharmaceutical world as an alternative treatment from natural ingredients, one of which is as an antibacterial. Staphylococcus aureus bacteria can cause skin infections such as boils. If it enters the bloodstream, it can cause meningitis or lung infections. This study aims to determine the total phenolic content in carrot leaves extracted with 70% and 96% ethanol solvents and to determine their antibacterial activity against Staphylococcus aureus. Carrot leaf extract is obtained by the maceration method. Total phenolic content was calculated using the Follin-Ciocalteau method. The antibacterial activity test was carried out using an excellent method. The research results showed that the yield of 70% ethanol extract was 17.235% and 96% ethanol extract was 16.053%. The results of testing the phenolic content of 70% ethanol extract of carrot leaves were 44.586 mgGAE/g and the phenolic content of 96% ethanol extract was 34.939 mgGAE/g. The results of the antibacterial activity test of 70% ethanol extract of carrot leaves had an average measurement of the inhibition zone at concentrations of 20%, 30% and 40%, namely 0.175 cm, 0.226 cm and 0.274 cm.